Genome-Wide Characterization and Expression Analysis of GeBP Family Genes in Soybean - Sushuang Liu; Yanmin Liu; Chundong Liu; Feixue Zhang; Jiaping Wei; Bingxuan Li (Plants, 2022)
The glabrous-enhancer-binding protein (GeBP) family is a family of plant-specific transcription factors, whose members share a central DNA-binding domain. Previous studies have already proven that GeBP genes are involved in the control of cell expansion but not cell proliferation in Arabidopsis. However, there has not yet been a versatile analysis of the GeBP genes’ function in soybean (Glycine max L.). Here, we identified and named 9 GmGeBP genes in the soybean genome. These genes were distributed on 7 of the 20 chromosomes and the intron numbers ranged from zero to one. According to the phylogenetic tree, 52 GeBP genes obtained from four plant species were clustered into major four groups. Through the RNA-seq analysis of the nine GmGeBP genes, 8 of 9 GmGeBP genes were be found to expressed differentially across the 14 tissues. Additionally, among nine GmGeBP genes, only GeBP4 were highly expressed in abnormal trichome soybeans, which was predicted to be involved in trichome development. This genome-wide analysis of GmGeBP genes helps to provide an overview of the evolution and functions of two kinds of soybean plants. These results will help to clarify the potential functions and characteristics of GmGeBP genes in the soybean life cycle.